Application of Speaking Public and E-Learning-Based Edmodo in History Learning - Rachmatsyah Rachmatsyah; Tengku Muhammad Sahudra; Irdalisa Irdalisa; Bagus Endri Yanto (STAI Hubbulwathan Duri, 2022)
Historical subjects must be able to accommodate Student Centered Learning. Communication skills, especially communicating in public (public speaking) must be owned by the teacher to make a short historical story through learning technology media. The purpose of this research is how the teacher understands the various techniques of Public Speaking and the application of edmodo-based applications in historical learning. The method used is descriptive analysis with a qualitative approach. Starting from the stage describing, analyzing, and comparing. Collecting data through a Library (Content Analysis), and documentation. The findings of this study are to produce good public speaking capabilities, the teacher must find Strong Why in him, communicate in learning with the following stages: (1) amazing opening; (2) Content; and; (3) Powerful Closing. Meanwhile Edmodo can be applied in one class, one school, between schools in Satukota/Regency. Edmodo can be used for students, teachers other than Edmodo are used to communicate by using social media models, Learning Materia, supporting Team Teaching, Co-Teacher, and Teacher Collaboration models.